INTELKAM UNIT EFFORTS THROUGH EARLY DETECTION ACTIVITIES TO PREVENT THE CRIME OF TWO WHEEL THEORY AT GROBOGAN POLRES - MUHAMAD YUSUF APRIAN (Advances in Police Science Research Journal, 2022)
The background of writing this final project is the large number of criminal acts of theft of two-wheeled vehicles at the Grobogan Police Station during the last five years. By prioritizing the preemptive method, the Intelkam Unit made efforts to prevent the crime of two-wheeled theft at the Grobogan Police by carrying out early detection activities to prevent the emergence of intentions and opportunities to commit crimes so as to create security and public order. The purpose of this paper is to find out how the implementation of the Intelkam Unit's early detection and the Intelkam Unit's efforts in carrying out early detection to prevent the crime of two-wheel theft. As an analytical tool, the author uses several theories and concepts, namely: management theory, crime prevention theory, effort concept, Intelkam Unit concept, early detection concept, crime prevention concept, and motor vehicle theft concept. With the research area at the Grobogan Police Station. This research was conducted with a qualitative approach, using the type of field research, as well as data collection techniques by observation, interviews, and document studies. The location of the research is in Grobogan Regency. The results of the study found that there were several problems in the implementation of early detection activities where problems were found at the planning, organizing, implementing and monitoring stages. For example, the absence of an activity plan, the lack of personnel to carry out tasks, the lack of cooperation with the surrounding Sector Police, and the absence of consolidation and analysis and evaluation. Several problems were also found in early detection efforts to prevent two-wheeled theft, such as the absence of early detection at the juvenile level, early detection efforts that have not been carried out in vulnerable hours and areas, and the absence of cooperation with the technical detective function after the completion of the investigation.